2022
DOI: 10.1111/acer.14943
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis on the association between theory of mind and alcohol problems in non‐clinical samples

Abstract: Background Deficits in theory of mind (ToM) found in individuals with alcohol use disorder (AUD) are often thought to result from prolonged heavy alcohol use. However, links between deficits in ToM and greater alcohol problems are often also present in non‐clinical samples (e.g., adolescents and young adults) who may not have a similar long‐lasting history of alcohol consumption as individuals with AUD. The current study is the first to systematically review and meta‐analyze results from studies examining asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…In line with findings in AUD populations, one meta-analysis that examined non-clinical samples found an association between lower ToM and more alcohol related problems 30 . Additionally, experimental studies in non-AUD individuals have found that drinking alcohol can have acute negative effects on social cognition processes such as facial emotion recognition, empathy and ToM (for a review, see 31 ).…”
Section: Introductionsupporting
confidence: 57%
“…In line with findings in AUD populations, one meta-analysis that examined non-clinical samples found an association between lower ToM and more alcohol related problems 30 . Additionally, experimental studies in non-AUD individuals have found that drinking alcohol can have acute negative effects on social cognition processes such as facial emotion recognition, empathy and ToM (for a review, see 31 ).…”
Section: Introductionsupporting
confidence: 57%
“…The results indicated a positive association between state affective empathy and number of standard drinks consumed. These findings add to a growing body of work highlighting the importance of social factors in alcohol use and misuse (e.g., Creswell, 2021;Fairbairn & Sayette, 2014;Fairbairn et al, 2015;Goodwin & Sayette, 2022;Kumar et al, 2022aKumar et al, , 2022b. Future research is needed to replicate these findings and explore possible mechanisms for the link between higher state affective empathy and increased alcohol use, as well as individual difference factors (e.g., drinking refusal self-efficacy, impulsivity; Creswell et al, 2019;Laghi et al, 2019) that might moderate the association between state affective empathy and alcohol use.…”
Section: Discussionmentioning
confidence: 60%
“…We systematically reviewed alcohol administration studies and found no consistent effects of any dosage of alcohol on recognition of any emotion. Further research is needed to clarify the underlying mechanisms explaining alcohol's effects on positive and negative social behaviours (e.g., changes in empathy and/or theory of mind) 46 , 81,82 …”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to clarify the underlying mechanisms explaining alcohol's effects on positive and negative social behaviours (e.g., changes in empathy and/or theory of mind). 46,81,82…”
Section: Discussionmentioning
confidence: 99%